Rapid genomic testing in critically ill pediatric patients: Genetic counseling lessons from a national program - Kirsten Boggs; Fiona Lynch; Michelle Ward; Sophie E. Bouffler; Samantha Ayres; Robin Forbes; Amanda Springer; Michelle G. de Silva; Elly Lynch; Lyndon Gallacher; Tenielle Davis; Ana Rakonjac; et al. (Genetics in Medicine Open)
Genetic counselors (GCs) face unique challenges in the acute care setting. Acute care environments—such as neonatal and pediatric intensive care units—are characterized by urgency, complexity, and rapid decision making. These settings require GCs to navigate a delicate balance between addressing the immediate clinical needs of patients and providing comprehensive genetic information to families, while demanding adaptation of existing skills for practice.Rapid genomic testing (rGT) is increasingly becoming standard of care in acute care. GCs are well placed to support families through the rGT process. Despite this, there is a lack of consistency in the provision of comprehensive acute care genetic counseling globally and a subsequent need for professional guidance in this area.The Acute Care Genomics study piloted a national approach to delivering rGT for infants and children admitted to intensive care units in Australia with suspected genetic conditions between 2018 and 2022. GCs from across Australia were involved in both pre- and post-test counseling for the families of these critically unwell children. Based on our collective experience of delivering this national rGT program, this article provides a discussion of common challenges for health professionals new to delivering rGT in intensive care. We share some practical solutions and make recommendations for supporting families in this area of practice.